ISLAMIC ECONOMY BETWEEN CONCEPTS AND METHODOLOGY THROUGH THE THOUGHTS OF MUHAMAD ANAS ZARQO - Fatma Wati Sungkawaningrum; Najib Mubarok (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2020)
Research on the Islamization of Economics between concepts and methodologies through the thoughts of Muhammad Anas Zarqo is about whether conventional economics that has been globalized have become Islamic economics? Is changing it to Islamic economics can change conventional global economic rules such as Islamic economic rules? This study aims to explain the relationship between Islamic economics and Islamic law and discuss proposed work plans for the Islamization of the economy. The research methodology used is ushul fiqh which applies in Islamic economics. The results of the study are that conventional economics and Islamic economics are actually not much different, the difference is the order of values and the consequences arising from the order of the rules in force. Islamic economics is divided into two parts: the first is the Islamic economic system; the second is an analysis of Islamic economics. Most of the first part is normative and discusses how economic life must be compatible with Islam. It also explains the economic reasons for sharia rules, seeking the help of Islamic economic analysis. The second conclusion is that there is a common interest between Islam and conventional economics.